Symptom evolution in rice genotypes under iron toxicity conditions - Shrestha, R. K.; Becker, M. (Journal of the Institute of Agriculture and Animal Science, 2018)
A greenhouse study was conducted in the University of Bonn, Germany during July-September, 2009 to comparatively evaluate six contrasting lowland rice genotypes, viz. IR31785, Nipponbare, WAS161, CK73, TOX3107 and Pokkali at increasing rates of Fe (II) under both dry and moist atmospheric conditions. Plants were grown in hydroponic culture for 35-days and subjected to 4-day Fe(II) pulses of 5 (control), 500, 1000 and 1500 mg Fe2+ L-1 under conditions of low (0.3Kpa) and high (2.4 Kpa) vapor pressure deficit. Rice genotypes expressed earlier and intense leaf bronzing symptoms with increasing Fe2+ stress and as the atmosphere became drier. However, genotypes significantly differed with regards to their response to iron stress. Some of the genotypes were able to maintain low leaf bronzing symptoms under higher level of iron stress and high vapor pressure deficit condition. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, Page: 147-150